Metal-Organic Frameworks/Graphene Oxide Composite: A New Enzymatic Immobilization Carrier for Hydrogen Peroxide Biosensors. Issue 3 (1st January 2016) - Fan, Zengjie; Wang, Jinqing; Nie, Yingying; Ren, Liling; Liu, Bin; Liu, Gang
Abstract : Enzymatic loss and inactivation are two main problems that can degrade the performance of biosensor. In order to resolve the problems, a new enzymatic immobilization carrier was developed by using biomimetic methods. Horseradish peroxidase (HRP) was initially encapsulated into zeolitic imidazolate frameworks (ZIFs) severed as protective structure. To overcome electron transfer barrier of ZIFs, graphene oxide (GO) of high conductive graphene precursor was used to enhance their conductivity. Subsequently, ZIFs@HRP/GO and GO-polyethyleneimine with opposite charges were alternatively assembled onto the substrate of indium tin oxide to construct multilayer films of the biosensor. Systematic characterizations showed that ZIF-8 with an average size of approximately 160.9 nm encapsulating HRP uniformly grew onto the surface of GO. The newly designed structure combined with the excellent properties of the GO and ZIFs guarantee easy, direct electrochemistry and good catalytic activity toward H2 O2 oxidation can be achieved with this biosensor. Electrochemical experiment study indicate that the resulting biosensor presented a wide linear range of 0.02–6 mmol/L, a low detection limit of 3.4 μmol /L (S/N = 3), excellent anti-interference ability, and long-term stability as well.